Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas 4 Menggunakan Kombinasi Model PBL, NHT, dan TGT - Azkia Quthrunnada; Ramadi (CV. ITTC INDONESIA, 2023)
The problem that is the focus of this research is the lack of student activity and learning outcomes. This is because learning is still one-way, lack of student participation and active role, and lack of student understanding of learning materials. This study aims to analyze the activities and learning outcomes of students in Civics subjects which include material on the diversity of individual characteristics in grade 4 students of SDN Sepakat Bersama Barito Kuala Regency using a combination of Problem Based Learning (PBL), Numbered Head Together (NHT), and Team Games Tournament (TGT) learning models. The approach used in this research is a qualitative approach in the form of Classroom Action Research (PTK) which was held for four meeting sessions. The 4th grade students of SDN Sepakat Bersama Barito Kuala Regency with a total of 9 people in semester 2 of the 2022/2023 school year became the main subject. The data contained in this study include qualitative and quantitative elements. Part of the data that focuses on qualitative aspects is obtained through observations of student activities. Meanwhile, data with quantitative aspects were obtained through the implementation of individual written tests. The process of data analysis in this research runs descriptive methods and is represented through a table, graph, and interpretation based on percentages. The results showed that student activity increased with a classical percentage of 89% of the criteria